Casa de Cultura de Santa Maria: restauração e readequação dos espaços de um patrimônio de Santa Maria/RS - Frota, Sadiana Luz Martins (2013)
We can avoid the loss of the existing heritage by making it object of study, thus contributing to value our historicity and preservationism. This paper aspires to better support the development project of Restoration and Readjustment of Casa de Cultura of Santa Maria through knowledge and preservation. The former Palácio da Justiça, where Casa de Cultura of Santa Maria currently is, was built in the 1940 s. It is preserved by heritage since 2009 by the City Hall as a Historic and Cultural Heritage of Santa Maria. The building has an Art Deco style. Its facade, rich in structural, keeps its original configuration. Nowadays, the Casa houses cultural and artistic associations and the Municipal Art School Eduardo Trevisan (EMAET), which offers courses in art history, theater, singing and music, held in inappropriate spaces though. Theoretical references were approached as sources for the development of this research, mainly Art Deco, besides concepts related to pathological manifestations and causes for degradation of historic buildings and their forms of representation. Considering all the objectives, such as detailing discovered problems and propose a plan for the preservation, a compromised state of conservation was verified, which accounts for the importance of the restoration project. Finally, as a preventive measure, a preservation plan is proposed, thus increasing the responsibility of future administrators of this building, so that it is kept in good state.